The 12th Symposium on Polar Science, Program and Abstracts, Session OS - 田中, 良昌; Tanaka, Yoshimasa (2021)
The 12th Symposium on Polar Science, 15–18 Nov. 2021, National Institute of Polar Research (NIPR) Research Organization of Information and Systems (ROIS) conference object